Online Pornography Consumption: Examining its Role in Sexual Motivation, Arousal, Gratification, and Problematic Use - Mohd Shahrul, Kamaruddin; Chong, Siew Kian; Muliana, Mohd Taha; Fatin Adha, Murad; Aini Azeqa, Ma’rof (UNIMAS Publisher, 2025)
This study examines the relationships between online pornography consumption, sexual motivation, arousal, and gratification, and their potential link to problematic pornography use, which is characterised by difficulties in controlling consumption despite negative consequences. A total of 202 individuals who engage in online pornography use participated in this research, which was conducted via an anonymous online questionnaire distributed across various digital platforms, including email groups and social media (e.g., Twitter, Facebook, WhatsApp). Convenience sampling was used to recruit participants. The findings reveal a strong positive correlation between online pornography consumption and an increased tendency towards problematic pornography use. Sexual arousal during pornography consumption was identified as the most significant predictor of problematic use. Furthermore, the reinforcing nature of pornography consumption, driven by motivation, arousal, and gratification, plays a crucial role in sustaining these behaviours. These findings are consistent with existing theoretical models of behavioural addiction, indicating that reinforcement mechanisms such as cue-reactivity and craving significantly contribute to the persistence of problematic pornography use. This study offers valuable insights into the psychosocial dynamics of online pornography consumption and highlights the importance of addressing its reinforcing effects to better understand and mitigate the potential risks associated with excessive or maladaptive use.